Strongyloides stercoralis hyperinfection after corticosteroid therapy: A report of two cases - Al Maslamani Mona; Al Soub Hussam; Al Khal Abdel Latif; Al Bozom Issam; Abu Khattab Mohammed; Chacko Kadavil (Annals of Saudi Medicine, 2009)
Two cases of Strongyloides stercoralis hyperinfection are described. Both patients were expatriates from the Indian subcontinent, and reported the use of corticosteroids. The first patient presented with severe pulmonary disease that necessitated respiratory support, followed by acute abdomen and intestinal obstruction and he succumbed to these diseases. The second patient also presented with acute pulmonary disease, which responded to antihelmintic treatment and supportive care; however, he died later due to his primary disease. The clinical features of S stercoralis hyperinfection are nonspecific; therefore, a high index of suspicion is required for early diagnosis and to start appropriate therapy. Because of the seriousness of the disease and the associated high mortality we suggest screening for S stercoralis in patients from endemic areas who will be taking immunosuppressive therapy.